POWER FACTOR CORRECTOR OF THE FREQUENCY-REGULATED ELECTRIC DRIVE - Букарос, Андрій Юрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The new method of the power factor correction of the frequency-regulated electric drives secondary power supply is offered. Comparing power descriptions of the offered power factor corrector is conducted to the existent technical decisions.